The Diverse Benefits of Alternate Wetting and Drying (AWD) - Allen, Justin; Sander, Björn Ole (2019)
Rice is a staple for half the world’s population, thus its impact on land and water use is immense. Standard production practices using continuous flooding (CF) are resource intensive and contribute significant global methane emissions. The technique of alternate-wetting-drying (AWD) uses a more controlled irrigation strategy that can significantly reduce methane emissions as well as water use and pumping costs. These three established benefits of AWD have been well documented in previous papers. Aside from these primary benefits, recent literature suggests there are many potential secondary benefits that have yet to be fully reviewed. These co-benefits and their site-specific conditions or limitations are reviewed in this paper.